2013
DOI: 10.1590/s0366-69132013000100017
|View full text |Cite
|
Sign up to set email alerts
|

Addition of sedimentary rock to kaolinitic clays: influence on sintering process

Abstract: The physical and mechanical properties of clay-based ceramic probes with sedimentary rock added as the non-plastic component were evaluated. Samples were prepared with 0, 20, 40, 60 and 80 wt.% of rock added to the clay material. Pressed (7 ton) probes were sintered at 500, 800, 900, 1000, 1100 and 1200 °C and submitted to X-ray diffraction analysis and technological characterization. The X-ray diffraction results showed that the sedimentary rock had micaceous clay minerals, while the clay material had kaolini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 11 publications
0
17
0
1
Order By: Relevance
“…These properties are linked to the amount of porogen and sintering temperature. Previous works in the field have shown that porosity of ceramic filters decreases with increase in firing temperature for the same composition of clay and porogen fired at different temperatures [4] and that the physico-chemical stability increases with increase in firing temperature due to the formation of more crystalline phase such as mullite [5]. But no matter the crystalline phase present in the material it's stability can be influenced by the physico-chemical properties of the feed water such as pH.…”
Section: Introductionmentioning
confidence: 99%
“…These properties are linked to the amount of porogen and sintering temperature. Previous works in the field have shown that porosity of ceramic filters decreases with increase in firing temperature for the same composition of clay and porogen fired at different temperatures [4] and that the physico-chemical stability increases with increase in firing temperature due to the formation of more crystalline phase such as mullite [5]. But no matter the crystalline phase present in the material it's stability can be influenced by the physico-chemical properties of the feed water such as pH.…”
Section: Introductionmentioning
confidence: 99%
“…Stoichiometric mullite (3Al 2 O 3 .2SiO 2 , known as mullite 3:2) is an important refractory material that has been synthesized by solid-state reaction (reactive sintering) of synthetic or natural raw materials such as aluminum isopropoxide, kaolin, alumina, silica, rice husk ash, and fly ash [1,2]. Such a mullitization reaction is a thermally activated process taking place through cationic (Al 3+ and Si 2+ ) diffusion at temperatures higher than 1300 °C [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…As expected, it was verified that the CDW had lower specific mass and unit mass. But it presented about seven times higher water absorption in relation to the natural aggregate (gravel), which was within the absorption parameter allowed by the standard (≤12%) [24,25], mainly due to its high porosity [9,12,26]. Also, the CDW specific mass was smaller than the reference aggregate [10], associated with the presence of more porous material in the residue composition.…”
Section: Resultsmentioning
confidence: 62%